Marine ice recycling at the southern McMurdo Ice Shelf, Antarctica. Issue 228 (2015) - Koch, Inka; Fitzsimons, Sean; Samyn, Denis; Tison, Jean-Louis
Abstract: Marine ice accretes at the base of ice shelves, often infilling open structural weaknesses and increasing ice-shelf stability. However, the timing and location of marine ice formation remain poorly understood. This study determines marine ice source water composition and origin by examining marine ice crystal morphology, water isotope and solute chemistry in ice samples collected from the southern McMurdo Ice Shelf (SMIS), Antarctica. The measured co-isotopic record together with the output of a freezing model for frazil crystals indicate a spatio-temporally varying water source of sea water and relatively fresher water, such as melted meteoric or marine ice. This is in agreement with the occurrence of primarily banded and granular ice crystal facies typical for frazil ice crystals that nucleate in a supercooled mixture of water masses. We propose that marine ice exposed at the surface of SMIS, which experiences summer melt, is routed to the ice-shelf base via the tide crack. Here frazil crystals nucleate in a double diffusion mechanism of heat and salt between two water masses at their salinity-dependent freezing point. Recycling of previously formed marine ice facilitates ice-shelf self-sustenance in a warming climate.